Characterization of a novel Toll-like receptor 13 homologue from a marine fish Nibea albiflora, revealing its immunologic function as PRRs. (February 2023) - Liu, Yue; Yang, Meijun; Tang, Xiuqin; Xu, Dongdong; Chi, Changfeng; Lv, Zhenming; Liu, Huihui
Abstract: Congenital immunity mediated by Toll-like receptor (TLR) family is the first line of defense for disease-resistant immunity of fish and plays a vital role as a bridge between innate immunity and acquired immunity. As a less known member of the TLR family TLR13 can participate in the immune and inflammatory reactions of the body for recognizing the conserved sequence of 23S rRNA in bacteria and induce immune response. In this study, the full-length cDNA of TLR13 from Nibea albiflora (named as NaTLR13 ) was cloned and was functionally characterized. It was 4210bp (GenBank accession no. MT701899) including an open reading frame (ORF) of 2886bp to encode 962 amino acids with molecular weight of 110.37 kDa and the theoretical isoelectric point of 9.08. There were several conservative structures in NaTLR13 such as 15 leucine-rich repeat sequences (LRRs), a Toll-IL-1 receptor domain (TIR), an LRR-CT terminal domain, two LRR-TYP structures and two transmembrane domains. The multiple sequence alignment and phylogenetic analysis manifested that NaTLR1 3 had high similarity with Larimichthys crocea and Collichthys lucidus (88.79% and 87.02%, respectively) and they fell into the same branch. The Real-time PCR showed that NaTLR13 was expressed in all selected tissues, with the highest in the spleen, followed by the liver, kidney, gill, heart and muscle. After being challenged by Vibrio alginolyticus, Vibrio parahaemolyticus or Poly (I:C), the expression of NaTLR13 increased firstly, then decreased and finally stabilized with time for its immune defense function. Subcellular localization analysis revealed that NaTLR13 was unevenly distributed in the cytoplasm with green fluorescence and MyD88 was evenly spread in the cytoplasm with red signals. When NaTLR13 and MyD88 were co-transfected, they obviously overlapped and displayed orange-yellow color, which showed that the homologous TLR13 might interact with MyD88 for NFκB signaling pathway transmission. The functional domains of NaTLR13 (named NaTLR13-TIR and NaTLR13-LRR) were expressed in E.coli BL21 (DE3) and purified by Ni-NAT Superflow Resin conforming to the expected molecular weights, and the recombinant proteins could bind to three Vibrios ( V.alginolyticus, V.parahaemolyticus and Vibrio harveyi ), indicating that NaTLR13 could be bounden to bacteria through its functional domain. These results suggested that NaTLR1 3 might play an important role in the defense of N.albiflora against bacteria or viral infection and the data would provide some information for further understanding the regulatory mechanism of the innate immune system in fish. Highlights: A TLR13 homologue was identified from Nibea albiflora (NaTLR13). NaTLR13 had highly conserved functional domains and located in cytoplasm. There might be the interaction between NaTLR13 and MyD88 for Toll/NF-κB pathway. NaTLR13 could be significantly induced in response to bacteria and viruses. NaTLR13-TIR and NaTLR13-LRR could couple to the pathogenic bacteria.